Insight into the source of grapevine water acquisition during key phenological stages using stable isotope analysis. (28th November 2017) - Karakis, S.; Gulbranson, E.; Cameron, B.
Abstract: Background and Aims: Stable isotope analysis of grapevine water provides insight into seasonal water use trends, soil depth of active water/nutrient uptake, and the role of water in the physiological processes of grapevines. This technique identifies the sources of water utilised and the functional rooting depth for vine water uptake over the growing season to support development of efficient irrigation strategies while managing grape and wine composition. Methods and Results: The hydrogen stable isotope ratio (δD) values of vine water identify rain as the principal water source during budburst and flowering/fruitset, and various combinations of rain and groundwater in summer and autumn, with an increasing proportion of groundwater in the mixture, as veraison/ripening continues and fruit maturity is achieved at harvest. The seasonal water use trend demonstrates a variable functional rooting depth for grapevine water acquisition over time, with the shallow roots utilising rain water as a main source in spring and a root system that can reach progressively deeper into the soil profile as the growing season advances. Conclusions: Water acquired by grapevines during the 2015 growing season originated from various depths and was derived from a combination of meteorological sources prior to recharging the soil water reservoir. The isotopic composition of grapevine water demonstrates that the functional rooting depth for water uptake is highly variable during the different phenological stages of the grapevines. Significance of the Study: The preferential vine water use allows irrigation recommendations to be made/forecasted to maximise water uptake efficiency and water conservation. This study site has an udic moisture regime, potentially providing insensitive isotopic variations due to the evenness of rainfall; thus, the success of this approach suggests that these methods will be highly effective in identifying seasonal patterns in ustic and xeric moisture regimes.